PENGEMBANGAN MEDIA VIDEO ANIMASI DENGAN MENGGUNAKAN APLIKASI ANIMAKER PADA PEMBELAJARAN TEMA CUACA DI KELAS III SEKOLAH DASAR - Siti Fadlina Ningrum; Sutarini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This development research project aims to (1) Develop animated video media using Animaker application on Weather theme learning, (2) Know the feasibility of animated video media using Animaker application on Weather theme learning. This research is a type of Research and Development (R&D) development research using the 4D model developed by Thiagarajan. In this study, researchers carried out the 4D development procedure only up to stage 3, namely Development, because the focus of this study was only to develop and determine the feasibility of animated video media using the Animaker application on weather theme learning. The subjects in this study were media expert validators, material experts and teacher responses. The instrument used in this research is a questionnaire. The analysis technique used is qualitative descriptive analysis technique. Based on the results of validation from media experts, a percentage of 85.3% was obtained with the criteria "very feasible". from the results of the validation of material experts, a percentage of 81.3% was obtained with the criteria "very feasible" and from the results of teacher response validation obtained at 90.6% with the criteria "very feasible". From the assessment obtained, it can be said that the animated video media using the weather theme Animaker application developed is "very feasible" to be used in the learning process.